DEVELOPMENT OF GIS BASIC KNOWLEDGE MODULES CLASS X IIS MAN 1 BANDAR LAMPUNG - Salsabila Ramadhania; Sugeng Widodo; Dian Utami (Journal Learning Geography, 2022)
This research is a development study that aims to develop geographic information system on basic knowledge materials geographic information systems and analyzing the level of feasibility and effectiveness of the geographic Information system module. The type of research used is RD (Research and Development) research with a 4D development model, developed by S. Thiagarajan et al. Based on the results of the study show that (1) the feasibility level of the module based on the assessment of the three experts get an average score of 3.10 with a very feasible category, (2) the feasibility level of the module based on the assessment of students in large group tests get an average score of 3.22 with a very feasible. For the level of effectiveness of the module measured the test results show an increase in value before and after using the module. At Pretest the mean score obtained by students was 60.68 and the mean score increased to 89.72 at Posttest.